Perbedaan Zakat, Infaq, Shadaqah, dan Waqaf serta Kedudukannya dalam Islam dan Mustahiqnya - Ana Syahroni; Saefulah Fatah; M Yuda (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Zakat, infaq, shadaqah, and waqf are important instruments in the Islamic economic system that aim to create social justice, wealth distribution, and public welfare. Although often understood overlappingly, each has different legal characteristics, distribution mechanisms, and beneficiaries (mustahiq). This article aims to outline the essential differences between the four instruments, examine their position in Islamic teachings, and explain the categories of beneficiaries. This study uses a descriptive qualitative approach with literature study as the main method. The results show that a comprehensive understanding of zakat, infaq, shadaqah, and waqf can improve the effectiveness of wealth distribution and social development of Muslims.